Keselamatan dan Kesihatan Pekerja (KKP): Kajian Kes Projek Pembinaan Jambatan, Negeri Kelantan : NONE - Mat Hussin, Muhammad Hafizzam; Shafii, Haryati; Md Yassin, Azlina; Khalid, Zailawati (Research in Management of Technology and Business, 2023)
The bridge construction project is one of the mega projects in Malaysia to improve the quality of existing roads to more efficient highways. The lack of safety and health among workers on the site should be worried. This study aims to identify factors that cause accidents among workers and suggest methods to reduce the accident rate at bridge construction sites. Qualitative methods are used through interviews with respondents to answer the objectives of the study. The researcher will use the semi-structured interview method with some important individuals at the bridge construction site consisting of consultants, contractors, and engineers involved in the construction of the bridge to achieve both objectives of the study. Data was collected through interviews and analyzed using thematic methods. The results of the study show all workers comply with PPE procedures at the bridge construction project site. In conclusion, this bridge construction project may result in accidents for its workers and road users because there are certain factors that cause accidents at the construction site and this matter needs to be resolved immediately by several authorities.   Keywords: Occupational Safety and Health (OSH), Bridge Construction Project, Construction Workers